Decreased resting-state functional connectivity of the habenula-cerebellar in a major depressive disorder - Jung, Ju-Yeon; Cho, Seo-Eun; Kim, Nambeom; Kang, Chang-Ki; Kang, Seung-Gul (Frontiers in Psychiatry, 2022)
Background: The habenula and septal nuclei are known as the key brain areas of depression in animal experiments. However, there was few magnetic resonance imaging (MRI) studies on the functional connectivity between these areas and the subcortical areas in human with major depression. We aimed to investigate the difference of resting state functional connectivity (RSFC) among the major regions of interest (ROI) in the subcortical areas including both habenula and septal nuclei. Methods: We performed the seed-to-voxel analysis to investigate the RSFC between both habenula and septal nucleus and other subcortical regions. Furthermore, ROI-to-ROI analysis was performed among the combinations of ROI pairs in the subcortical areas. Results: The seed-to-voxel analysis showed lower RSFC between left habenula and the cerebellum in major depressive disorder (MDD) than in healthy controls (HCs). As a result of ROI-to-ROI analysis in subcortical areas, a total of 31 pairs of FCs in the MDD group showed lower RSFC than the HCs group. Conclusion: This study revealed a lower RSFC between the left habenula and cerebellum in patients with MDD and reduced RSFC among numerous subcortical areas. These new findings on the neural circuitry of MDD might contribute to an in-depth understanding of depression.